Academics' Attitudes toward Engaging in Public Discussions – Experimental Evidence on the Impact of Engagement Conditions - Vitus Püttmann; Jens Ruhose; Stephan L. Thomsen (Center for Economic Studies and ifo Institute (CESifo), 2021)
Academics are increasingly expected to engage in public discussions. We study how engagement conditions affect academics' engagement attitudes via a survey experiment among 4,091 tenured professors in Germany. Consistent with the crowding-out of intrinsic motivation, we find lesspositive attitudes when emphasizing public authorities' demands and public expectations regarding science's societal relevance. Effects are particularly strong among professors endorsing science–society relations. Moreover, effects are similar when highlighting risks associated with engagement, but more pronounced for females, and absent when emphasizing public support for academics' engagement. We conclude that considering individual incentive structures and safeguarding against repercussions may promote academics' engagement.
Keywords: I23; O33; 330; science communication; public engagement; professor; survey experiment; intrinsic motivation